Porphyromonas gingivalis Promotes Oral Squamous Cell Carcinoma Progression in an Immune Microenvironment. (June 2020) - Wen, L.; Mu, W.; Lu, H.; Wang, X.; Fang, J.; Jia, Y.; Li, Q.; Wang, D.; Wen, S.; Guo, J.; Dai, W.; Ren, X.; et al.
Increasing evidence has revealed a significant association between microorganisms and oral squamous cell carcinoma (OSCC). Porphyromonas gingivalis, the keystone pathogen in chronic periodontitis, is considered an important potential etiologic agent of OSCC, but the underlying immune mechanisms through which P. gingivalis mediates tumor progression of the oral cancer remain poorly understood. Our cohort study showed that the localization of P. gingivalis in tumor tissues was related to poor survival of patients with OSCC. Moreover, P. gingivalis infection increased oral lesion multiplicity and size and promoted tumor progression in a 4-nitroquinoline-1 oxide (4NQO)–induced carcinogenesis mouse model by invading the oral lesions. In addition, CD11b + myeloid cells and myeloid-derived suppressor cells (MDSCs) showed increased infiltration of oral lesions. Furthermore, in vitro observations showed that MDSCs accumulated when human-derived dysplastic oral keratinocytes (DOKs) were exposed to P. gingivalis, and CXCL2, CCL2, interleukin (IL)–6, and IL-8 may be potential candidate genes that facilitate the recruitment of MDSCs. Taken together, our findings suggest that P. gingivalis promotes tumor progression by generating a cancer-promoting microenvironment, indicating a close relationship among P. gingivalis, tumor progression of the oral cancer, and immune responses.